Significance of Cu-Fe3O4 on fractional Maxwell fluid flow over a cone with Newtonian heating - Hanifa Hanif; Arshad Khan; Mohd Rijal Illias; Sharidan Shafie (Journal of Taibah University for Science, 2024)
The goal of this research is to investigate fractional Maxwell hybrid nanofluids utilizing partial differential equations in terms of Caputo time fractional derivatives. Specifically, the effect of Newtonian heating on the thermal performance of a fractional Maxwell hybrid nanofluid moving over a permeable cone in the presence of thermal radiation and heat generation is considered. The Crank–Nicolson method and L1 algorithmt of Caputo derivative are used to find numerical solutions to the considered nonlinear problem. The effects of significant flow factors on fluid properties are examined and illustrated in various graphs. According to the results, the thermal performance of the fluid raised by 0.4%, 6.1%, and 3.1% on adding 4% volume fraction of [Formula: see text], [Formula: see text], and [Formula: see text], respectively, in the base fluid.